Investigation of nano iron carbide production by ball milling - Evin, E. (Natl Inst Optoelectronics, 2015)
In this study, two routes were used in order to produce iron carbide. Graphite powders were amorphisized and reduced to nano-size by ball milling process for C source. And also, nano-porous hematite powders were produced by thermomechanical method. In first route all powders, graphite and hematite were milled individually. In second route, both graphite and hematite were milled together up to 20 hours in a planeter ball mill. The nano-sized powders obtained from route one and two were compacted in order to make pellets. Then, these compacts were sintered in different temperatures between 800, 900 and 1000 C. The samples were investigated by X- Ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Transmission Electron Microscopy (TEM) and Wavelength Dispersive X-Ray (VVDX) in order to determine structural and morphological changes.
Keywords: Nano-iron carbide; Nano-porous hematite; Ball milling